Harnessing the job creation capacity of young rural agripreneurs: A quasi-experimental study of the ENABLE program in Africa - Adeyanju, Dolapo; Mburu, John; Gituro, Wainaina; Chumo, Chepchumba; Mignouna, Djana B.; Mulinganya, Noel (Elsevier, 2024)
With evidence of increasing investment in youth agribusiness empowerment programs across Africa, employment discussions and strategies are increasingly focusing on how youth-owned agribusinesses can facilitate long-term job creation and contribute to revitalizing rural economies in the coming years. In light of these changing employment dynamics, we assessed the evolving role of youth and small agribusinesses in employment creation in rural areas. Further, we assessed the impact of agribusiness empowerment programs in unlocking the job creation capacity of young agribusiness owners, taking evidence from the youth component of the African Development Bank (AfDB) Technologies for African Agricultural Transformation (TAAT) program, Empowering Novel Agribusiness-Led Employment (ENABLE) implemented in Kenya, Nigeria, and Uganda. A total of 1435 respondents, comprising 737 participants and 698 non-participants were surveyed across the three countries. An Endogenous Switching Regression (ESR) model was used to identify factors that determined program participation, and factors influencing job creation, and assess the program's impact on job creation. The results validate our assumption of changing employment dynamics in the rural areas where youth-owned small agribusinesses hired an average of 4 employees. The ESR results show the significance of the program on the job creation capacity of participants across the three countries. Also, we found that non-participants could potentially increase their job creation capacity if they had participated in the program. Factors that influence job creation include socio-economic, such as age and marital status, business attributes including agribusiness experience, business level, income, and access to land. These results indicate that continuous concerted efforts on agribusiness empowerment will have a notable impact in generating more jobs and reducing the rates of unemployment, particularly among young people. Thus, more investment should be directed towards empowering young people in agribusiness in the study countries, and elsewhere in Africa.